2021
DOI: 10.21037/apm-20-1183
|View full text |Cite
|
Sign up to set email alerts
|

Risk predictive models for delirium in the intensive care unit: a systematic review and meta-analysis

Abstract: Background: An emerging approach to prevent delirium in an intensive care unit is the use of risk prediction models. At present, there is no scientific comparison of the predictive effect of the prediction model. This systematic review and meta-analysis aimed to compare the performance of available delirium risk prediction models for intensive care units.Methods: As of June 1st, 2019, articles on delirium prediction models of the intensive care patients were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Such methods are relevant for understanding the problem of delirium and its consequences in terms of clinical outcomes. For predictive models, instead, logistic regression [ 25 , 26 ] is mostly used, recently with machine learning technique [ 27 ]. The Cox model (CM) is used when considering time to define the probability of developing an event.…”
Section: Introductionmentioning
confidence: 99%
“…Such methods are relevant for understanding the problem of delirium and its consequences in terms of clinical outcomes. For predictive models, instead, logistic regression [ 25 , 26 ] is mostly used, recently with machine learning technique [ 27 ]. The Cox model (CM) is used when considering time to define the probability of developing an event.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fluctuating characteristics of delirium, non‐delirious patients may become delirious suddenly which required adjustment of restraint level. Integration of a tool that integrated delirium prediction models and has been shown with good performance in the ICU, such as E‐PRE‐DELIRIC and PRE‐DELIRIC (Chen et al, 2020), may further improve the accuracy of restraint decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fluctuating characteristics of delirium, non-delirious patients may become delirious suddenly which required adjustment of restraint level. Integration of a tool that integrated delirium prediction models and has been shown with good performance in the ICU, such as E-PRE-DELIRIC and PRE-DELIRIC(Chen et al, 2020), may further improve the accuracy of restraint decision making.5 | CONCLUSIONThe Restraint Decision Tree was shown to be feasible, acceptable, and usable in critically ill adult patients, which significantly minimizes restraint use with no increase in accidental catheter removal. Our study is a further key initiative to enhance the appropriate use of restraint in the ICU.…”
mentioning
confidence: 96%
“…Three recent systematic reviews found 26 unique prediction models for predicting delirium in ICU [9,12,13]. Of these models, 4 were identified by the review papers to be "dynamic" models: DYNAMIC-ICU [14], Auto-DelRAS [15], ABD-pm [16], and a model developed by Oh et al [17].…”
Section: Related Workmentioning
confidence: 99%